ANTIBIOTIC- ASSOCIATED RISK THE REDUCTION OF LACTOBACILLUS SPP. IN THE INTESTINAL MICROBIOTA IN PATIENTS WITH URINARY TRACT INFECTIONS - N. Stepanova; N. Stashevska; L. Lebid; S. Savchenko; M. Kolesnyk (Український Журнал Нефрології та Діалізу, 2017)
The aim of our study was to evaluate a risk reduction of indigenous gut microbiota in patients with urinary tract infection (UTI, associated with the intake of antibacterial medicinal products